2021
DOI: 10.1007/s00253-021-11489-3
|View full text |Cite
|
Sign up to set email alerts
|

Marine dissolved organic matter: a vast and unexplored molecular space

Abstract: Marine dissolved organic matter (DOM) comprises a vast and unexplored molecular space. Most of it resided in the oceans for thousands of years. It is among the most diverse molecular mixtures known, consisting of millions of individual compounds. More than 1 Eg of this material exists on the planet. As such, it comprises a formidable source of natural products promising significant potential for new biotechnological purposes. Great emphasis has been placed on understanding the role of DOM in biogeochemical cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 145 publications
(196 reference statements)
0
22
0
Order By: Relevance
“…Previous results of nutrient amendment experiments from temperate regions indicate that organic substrates (glucose, dissolved free amino acids, and plankton extract) enhance heterotrophic metabolism more than inorganic substrates (NH 4 + , PO 4 3− ) (Church et al, 2000; Kirchman, 1990, 2000). Natural nutrient sources consist of exuded organic and inorganic substrates, with yeast extract resembling the former (Catala et al, 2021; Sundh, 1992). Active remineralization by protozoo‐ and metazooplankton probably also played a role in our experiment, providing nutrients and organic substrates from consumed prey.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results of nutrient amendment experiments from temperate regions indicate that organic substrates (glucose, dissolved free amino acids, and plankton extract) enhance heterotrophic metabolism more than inorganic substrates (NH 4 + , PO 4 3− ) (Church et al, 2000; Kirchman, 1990, 2000). Natural nutrient sources consist of exuded organic and inorganic substrates, with yeast extract resembling the former (Catala et al, 2021; Sundh, 1992). Active remineralization by protozoo‐ and metazooplankton probably also played a role in our experiment, providing nutrients and organic substrates from consumed prey.…”
Section: Discussionmentioning
confidence: 99%
“…Pooled EMs issued from different marine organisms constitute chemical seascapes made of thousands of distinct molecules in trace amounts (ppm, mg/L), often summarized as marine DOM. Due to their complexity, the composition of chemical seascapes has been barely explored. , Therefore, as suggested by Kelly et al, characterizing the molecular diversity of discrete source of marine EM will help not only to decipher the complexity of each chemical seascape but also to identify the ecological functions related to specific EM and possibly uncover new metabolites with biological potentials. Targeted studies performed with a few sponge species (namely, Aplysina fistularis, Agelas conifera, Aplysilla rosea, and also Crambe crambe , ) revealed that some of their specialized metabolites could be detected in the surrounding seawater.…”
Section: Introductionmentioning
confidence: 99%
“…The reactivity of marine dissolved organic matter (DOM) remains at the forefront of global carbon research. However, our understanding of dissolved organic carbon (DOC) turnover is hampered by its sluggish decomposition, making direct comprehensive decomposition studies prohibitive, given the extremely large time scale from hours to decades or even longer turnover times. Consequently, our current working knowledge is inferred from chemical proxies, metabolic measurements, and C flux budgets that do not take into account DOM sources outside the photic zone.…”
Section: Perspectivementioning
confidence: 99%